T2∗ relaxometry of fetal brain at 1.5 Tesla using a motion tolerant method - Vasylechko, Serge; Malamateniou, Christina; Nunes, Rita G.; Fox, Matthew; Allsop, Joanna; Rutherford, Mary; Rueckert, Daniel; Hajnal, Joseph V. (Magnetic Resonance in Medicine, 2015)
Purpose The aim of this study was to determine T2∗ values for the fetal brain in utero and to compare them with previously reported values in preterm and term neonates. Knowledge of T2∗ may be useful for assessing brain development, brain abnormalities, and for optimizing functional imaging studies. Methods Maternal respiration and unpredictable fetal motion mean that conventional multishot acquisition techniques used in adult T2∗ relaxometry studies are not practical. Single shot multiecho echo planar imaging was used as a rapid method for measuring fetal T2∗ by effectively freezing intra-slice motion. Results T2∗ determined from a sample of 24 subjects correlated negatively with gestational age with mean values of 220 ms (±45) for frontal white matter, 159 ms (±32) for thalamic gray matter, and 236 ms (±45) for occipital white matter. Conclusion Fetal T2∗ values are higher than those previously reported for preterm neonates and decline with a consistent trend across gestational age. The data suggest that longer than usual echo times or direct T2∗ measurement should be considered when performing fetal fMRI to reach optimal BOLD sensitivity. Magn Reson Med 73:1795-1802, 2015.
CRIS-Team Scopus Importer:2023-03-08
Keywords: fetus; fMRI; relaxometry; T2∗